2023
DOI: 10.1126/science.abj8379
|View full text |Cite
|
Sign up to set email alerts
|

USB1 is a miRNA deadenylase that regulates hematopoietic development

Abstract: Mutations in the 3′ to 5′ RNA exonuclease USB1 cause hematopoietic failure in poikiloderma with neutropenia (PN). Although USB1 is known to regulate U6 small nuclear RNA maturation, the molecular mechanism underlying PN remains undetermined, as pre-mRNA splicing is unaffected in patients. We generated human embryonic stem cells harboring the PN-associated mutation c.531_delA in USB1 and show that this mutation impairs human hematopoiesis. Dysregulated microRNA (miRNA) levels in USB1 mutants during blood develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a kind of single-stranded noncoding RNA composed of 18–24 nucleotides, which participate in the regulation of many physiological processes by controlling mRNA translation. A great deal of research evidence identify that the imbalance of specific miRNA expression is closely related to the occurrence of cancer or other pathological conditions, so some specific miRNAs have been identified as biomarkers for cancer diagnosis, therapy, and prognosis. Pancreatic ductal adenocarcinoma (PDAC) is considered to be one of the mortal neoplasms with the worst prognosis, which is difficult to diagnose at an early stage. Previous studies have demonstrated that miRNA-196a is significantly upregulated but miRNA-217 is markedly downregulated in PDAC, while miRNA-217 was highly expressed and miRNA-196a was low expressed in normal pancreas . Therefore, exploring simultaneous ultrasensitive detection and precise colocalization imaging of miR-217 and miR-196a in living cells holds immense importance in the early diagnosis of pancreatic cancer and ensure detection specificity.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a kind of single-stranded noncoding RNA composed of 18–24 nucleotides, which participate in the regulation of many physiological processes by controlling mRNA translation. A great deal of research evidence identify that the imbalance of specific miRNA expression is closely related to the occurrence of cancer or other pathological conditions, so some specific miRNAs have been identified as biomarkers for cancer diagnosis, therapy, and prognosis. Pancreatic ductal adenocarcinoma (PDAC) is considered to be one of the mortal neoplasms with the worst prognosis, which is difficult to diagnose at an early stage. Previous studies have demonstrated that miRNA-196a is significantly upregulated but miRNA-217 is markedly downregulated in PDAC, while miRNA-217 was highly expressed and miRNA-196a was low expressed in normal pancreas . Therefore, exploring simultaneous ultrasensitive detection and precise colocalization imaging of miR-217 and miR-196a in living cells holds immense importance in the early diagnosis of pancreatic cancer and ensure detection specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Hypofunctioning variants in USB1 (aka c16orf57 or Mpn1), a U6 spliceosome component, have been identified as the genetic cause of PN 3–6 . Previous in vitro studies on PN have focussed on the causation of neutropenia 8–11 . However, a cohesive explanation of how these pathogenic biallelic USB1 variants cause the pleotropic manifestations of the disease has not been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Previous in vitro studies on PN have focussed on the causation of neutropenia. [8][9][10][11] However, a cohesive explanation of how these pathogenic biallelic USB1 variants cause the pleotropic manifestations of the disease has not been advanced.…”
mentioning
confidence: 99%
“…3 USB1 encodes a conserved 3′ to 5′ RNA exonuclease processing U6 and U6atac spliceosomal small nuclear RNAs which acts as microRNA de-adenylase to regulate haematopoietic development. 4 The two siblings investigated were reported to harbour the USB1 homozygous mutation c.266-1G>A (p.E90SfsTer8) affecting the intron 2 acceptor splice site and causing mis-splicing of intron 2 and aberrant transcripts predicted to give rise to defective proteins. 5,6 Parajuli et al studied the younger proband who had developed a fistula in ano, which had not healed after 10 months of systemic and intralesional GM-CSF treatment.…”
mentioning
confidence: 99%
“…2 Finally, the insights offered by Parajuli et al have translational relevance as they may drive preclinical studies aimed at providing targeted treatment by exploring the changes in the transcriptional programme of PN i-PSC-derived myeloid precursors induced in differentiated cells by (epi)drugs and/or aptamers with demonstrated therapeutic potential in PN preclinical models. 4,10 ORC I D Lidia Larizza https://orcid.org/0000-0002-1367-7227…”
mentioning
confidence: 99%